2009
DOI: 10.1007/bf03161090
|View full text |Cite
|
Sign up to set email alerts
|

Urinary elimination kinetics of acephate and its metabolite, methamidophos, in urine after acute ingestion

Abstract: INTRODUCTIONAcephate (AP) is one of the few commercially available, over-thecounter organophosphorus (OP) insecticides in the US. It is considered one of the safest OP insecticides because of its low mammalian toxicity, with a lethal dose (LD50) of 360 mg/kg in mice and 900 mg/kg in rats [1]. The selective toxicity of AP is due reportedly to differential bioactivation and metabolism in insects compared to mammals; however, the exact mechanism is still unknown. In insects, AP is rapidly and extensively metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…One concern with silver usage is that the ketone moiety uniquely differentiates acephate from its degradation product–metabolite methamidophos. 52 The SERS spectrum of methamidophos is presented in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…One concern with silver usage is that the ketone moiety uniquely differentiates acephate from its degradation product–metabolite methamidophos. 52 The SERS spectrum of methamidophos is presented in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…One of the concentrations of methamidophos exposure (25 ÎŒg/L) is close to environmentally relevant concentrations of methamidophos in the water environment of some regions, such as Philippines, India and other countries [ 28 ]. Besides, another concentration (500 ÎŒg/L) is near to the level of methamidophos in part of the human samples [ 29 , 51 , 52 ], which indicates that people in some countries are exposed to methamidophos in dangerous levels. Besides, many studies have reported that methamidophos concentration in fresh fruits and vegetables were higher than the FAO/WHO permissible limits residual levels [ 7 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was therefore designed to study methamidophos neurotoxicity and related mechanism in the early stages of zebrafish. Two environmentally relevant concentrations of methamidophos (25 and 500 ÎŒg/L) were selected, which were according to the concentration in water environment and the level in part of the human samples, respectively [ 28 , 29 ]. The analysis of locomotor behavior and apoptosis was used to assess the impairment of nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…A 4 year old child who had ingested acephate was brought to an emergency room exhibiting profound generalized weakness and depressed gag reflex (155). The child was placed on mechanical ventilation, given intravenous fluids, and vasopressors, and atropine and pralidoxime, monitored for 32 days and released.…”
Section: Human Experiencementioning
confidence: 99%